Penerapan Model Pembelajaran Preview, Question, Read, Reflect, Recite, Review (PQ4R) untuk Meningkatkan Hasil Belajar Membaca Pemahaman Siswa Kelas V UPTD SD Negeri 28 Barru - Abd Halik; Nur Ilmi; Rosdiah Salam; Asriani As (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study examines the application of the Preview, Question, Read, Reflect, Recite, Review (PQ4R) learning model to improve reading comprehension learning outcomes for fifth grade students of UPTD SD Negeri 28 Barru. The approach used is a qualitative approach and the type of research is classroom action research (CAR). The subjects in this study were teachers and students of class V UPTD SD Negeri 28 Barru with a total of 14 students consisting of 6 boys and 8 girls. This study consisted of 2 cycles and each cycle consisted of 1 meeting. The data collection techniques used were observation, tests and documentation. Based on the research data in the first cycle the teacher's observations are in category C, the results of student observations are in category C and student learning outcomes show 43% completeness and are in category K. In cycle II the teacher's observations are in category B, the results of student observations are in category B and student learning outcomes show completeness of 79% and are in category B. Reading comprehension of class V UPTD SD Negeri 28 students Barru.